(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rinnamang S, Sirirueang K, Supavetch S, Meunpong P. 2020. Estimation of aboveground biomass using aerial photogrammetry from unmanned aerial vehicles in teak (Tectona grandis) plantation in Thailand. Biodiversitas 21: 2369-2376. Thailand is one of the best teak planting locations in the world. Teak is one of the most species planting and a significant source of high-value timber in Thailand. For plantation management, biomass is one of the important factors while determining the production of a plantation and also for sustainable forest management. Unmanned Aerial Vehicles (UAV) have the ability to produce 3D RGB digital images which can be used to study the plantation characteristics. This study aimed to use aerial images and photogrammetry techniques derived from unmanned aerial vehicles (UAV) to estimate teak biomass in Thong Pha Phum plantation, Kanchanaburi Province, Thailand. We conducted our study on 15-and 36-year-old teak stands, and compared the tree dimension between data obtained from field measurement and that from aerial images and photogrammetry techniques. In the 15-year-old stand, the average tree height estimated from the UAV and ground-truthing were 12.34 and 13.06 m, respectively. In the 36-year-old stand, the average tree height from the UAV and ground-truthing were 28.87 and 29.39 m, respectively. We found that in both stands, the difference between data generated from the UAV and ground-truthing data was not significant (p-value = 0.07 and 0.306, respectively). There was also a strong correspondence between tree height estimated from the UAV and that measured on the ground which is indicated by the high R2 (i.e. 0.70 and 0.64 for the 15-and 36-year-old stands, respectively). Using UAV generated data, the total biomass of 15-and 36-year-old stands was estimated to be around 42.07 t ha-1 and 67.13 t ha-1, respectively. The overall results suggest that UAV can be used as an effective tool to survey and monitor stand’s productivity in teak plantation.